MODEL PENINGKATAN PARTISIPASI MASYARAKAT DAN PENGUATAN SINERGI DALAM PENGELOLAAN SAMPAH PERKOTAAN * - Dwiyanto, Bambang Munas (Universitas Muhammdaiyah Surakarta, 2011)
The study aims to find a model of improving a communityâs role in the management in town area, particularly household rubbish. The early stage of the study was to analyze a management in town area, located at the Sub-District of Sambiroto, District of Tembalang, Semarang City. To analyze the stakeholders, it was necessary to study and discuss (focus group discussion) the management with them for finding an insight to develop the most appropriate model. The approach used to develop a Community-Based Integrated Rubbish Management was a community empowering through improving the stakeholdersâ role. The tested model took a trial and error as well as two-year observation, at least, with the experiment at different locations. A community-based household rubbish management system with a 3 R principle by separating rubbish could reduce a 70 percent rubbish volume.